2009
DOI: 10.1177/0961203308100512
|View full text |Cite
|
Sign up to set email alerts
|

Circulating chromatin–anti-chromatin antibody complexes bind with high affinity to dermo-epidermal structures in murine and human lupus nephritis

Abstract: Murine and human lupus nephritis are characterized by glomerular deposits of electron-dense structures (EDS). Dominant components of EDS are chromatin fragments and IgG antibodies. Whether glomerular EDS predispose for similar deposits in skin is unknown. We analysed (i) whether dermo-epidermal immune complex deposits have similar molecular composition as glomerular deposits, (ii) whether chromatin fragments bind dermo-epidermal structures, and (iii) whether deposits in nephritic glomeruli predispose for accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…We find it plausible to interpret the tissue co-localization of IgG, C1q and CRP as ICs containing [49]. Indeed, also nucleosomes/chromatin is a well-recognized constituent in ICs from LN patients [50].…”
Section: Discussionmentioning
confidence: 99%
“…We find it plausible to interpret the tissue co-localization of IgG, C1q and CRP as ICs containing [49]. Indeed, also nucleosomes/chromatin is a well-recognized constituent in ICs from LN patients [50].…”
Section: Discussionmentioning
confidence: 99%
“…This result explains the systemic character of tissue damage in SLE. Comparative studies of components of immune complexes and their localization in skin and glomerulus membranes and matrices demonstrated that they have similar structure (99,100). However, deposition of immune complexes in glomeruli did not predict deposition in skin.…”
Section: Origin Of Exposed Glomerular Chromatinmentioning
confidence: 99%
“…These autoantibodies form complexes with nucleosomes that deposit within the kidney and the skin [2], and the affection of the kidney causes a most serious and potentially fatal complication in human SLE; lupus nephritis [3]. Other nuclear autoantibodies like anti-nucleosome, anti-nucleolin and anti-centromere protein antibodies has been implicated in the development of lupus nephritis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%